(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The integration of Augmented Reality (AR) and Virtual Reality (VR) has redefined the creative language of design and cinema by transforming how stories are visualized, experienced, and interpreted. This study examines how these immersive technologies extend beyond conventional screen-based narratives to establish new modes of spatial storytelling and participatory engagement. AR and VR enable designers and filmmakers to merge physical and digital realities, fostering interactive environments where audiences become active participants rather than passive viewers. The paper analyzes global and Indian examples to explore how immersive media influences production design, narrative construction, and sensory experience. It also investigates how AR and VR are reshaping creative education, visual aesthetics, and audience perception through real-time interaction, multisensory feedback, and user-centered storytelling. By situating these developments within post-digital design theory, the research highlights the emergence of a new design language that blurs boundaries between art, technology, and human experience. This evolving paradigm underscores the need to view AR and VR not merely as tools but as transformative mediums shaping the future discourse of visual communication and cinematic design.